Death with a double edge [large type] - Perry, Anne (Perry, Anne. Daniel Pitt novel., 2021)
"When junior lawyer Daniel Pitt is summoned to the scene of a murder in the London district known as Mile End, he only knows that the victim is a senior lawyer from the same firm. What was this respected colleague doing in such a rough part of the city? The firm's head, Marcus fford Croft, may know more than he admits, but fford Crofts's memory is not what it used to be. Daniel finds his path blocked by officials at every turn, his investigation so unwelcome that even Daniel's father, head of Special Branch, Sir Thomas Pitt, receives a chilling warning from a powerful source. Suddenly, not just Daniel but his whole family is in danger"--Page 4 of cover.